Provenances of Cenozoic sediments in the Jianghan Basin and implications for the formation of the Three Gorges. Issue 16 (2nd November 2019) - Yang, Chaoqun; Shen, Chuanbo; Zattin, Massimiliano; Yu, Wu; Shi, Shaoxian; Mei, Lianfu
ABSTRACT: The formation of the Three Gorges (TG), the most important capture point along the Yangtze River, has been debated since the last century. Most of hypotheses on its formation are based on the timing of unconformities detected in the sedimentary basins along the riverbed. These unconformities may mark periods of tectonic activity and enhanced hydrodynamic condition. Herein, we detail the Cenozoic sedimentary provenance of the Jianghan Basin through LA-ICP-MS zircon U-Pb geochronology and heavy mineral analyses. The obtained data suggest that during Palaeocene-Oligocene time, the Jianghan Basin was supplied by sediments from the nearby mountain belts. However, the occurrence of zircons with ages <32 Ma above the unconformity at 24.6 Ma indicates a provenance from Cenozoic igneous rocks which are exposed only in the Qiangtang Block and the Songpan-Ganzi Orogen. We propose therefore that the TG formed between the late Oligocene and the early Miocene and that the 24.6 Ma unconformity in the Jianghan Basin represents the best dating of the TG formation.